Synthesis of Blue‐, Green‐, Yellow‐, and Red‐Emitting Graphene‐Quantum‐Dot‐Based Nanomaterials with Excitation‐Independent Emission. (28th December 2015) - Ke, Chia‐Chun; Yang, Ya‐Chun; Tseng, Wei‐Lung
Abstract : A one‐pot method is described for the preparation of graphene quantum dots/graphene oxide (GQDs/GO) hybrid composites with emission in the visible region, through heteroatom doping and hydroxyl‐radical‐induced decomposition of GO. The NH4 OH‐ and thiourea‐mediated dissociation of H2 O2 produces hydroxyl radicals. Treatment of GO with hydroxyl radicals results in the production of small‐sized GO sheets and GQDs, which self‐assemble to form GQDs/GO through strong π–π interactions. For example, the reaction of GO with a mixture of NH4 OH and H2 O2 for 40, 120, and 270 min generates yellow‐emitting GQDs/GO (Y‐GQDs/GO), green‐emitting GQDs/GO, and blue‐emitting GQDs, while red‐emitting GQDs/GO (R‐GQDs/GO) are prepared by incubating GO with a mixture of thiourea and H2 O2 . From the analysis of these four GQD‐based nanomaterials by transmission electron microscopy, atomic force microscopy, and fluorescence lifetime spectroscopy, it is found that this tunable fluorescence wavelength results from the differences in particle size. All four GQD‐based nanomaterials exhibit moderate quantum yields (1–10%), nanosecond fluorescence lifetimes, and excitation‐independent emissions. Except for R‐GQDs/GO, the other three GQD‐based nanomaterials are stable in a high‐concentration salt solution (e.g., 1.6m NaCl) and under high‐power irradiation, enabling the sensitive (high‐temperature resolution and large activation energy) and reversible detection of temperature change. It is further demonstrated that Y‐GQD/GO can be used to image HeLa cells. Abstract : Graphene oxide with adsorbed graphene quantum dots (GQDs/GO) is prepared by hydroxyl‐radical‐induced decomposition of graphene oxide and heteroatom doping. The four GQD‐based nanomaterials emit fluorescence in blue, green, yellow, and red colors with excitation‐independent emission. Except for the red‐emitting GQDs/GO, the other nanomaterials are stable in high‐concentration salt solution and under high‐power irradiation, making them potentially useful in temperature sensors and cellular imaging.